Peningkatan Partisipasi Peserta Didik Dengan Menerapkan Pendekatan Pembelajaran Teaching at The Right Level Pada Sub-Topik Materi Refleksi Fungsi Kelas XII di SMA Negeri 2 Makassar: Increasing Student Participation by Applying the Teaching at the Right Level Learning Approach to the Sub-topic of Reflection Material for Class XII Functions at SMA Negeri 2 Makassar - Nadzra, Nadzra (Jurusan Pendidikan Teknik Elektro, 2025)
This classroom-based action research aims to find out to what extent the influence of the application of Teaching at the Right Level is for the improvement of learning participation of Grade XII.10 students at SMA 2 Makassar. This research was conducted through involving 35 students. It was worked in two cycles which consist of several phases, namely planning, implementation, observation, and reflection. The data collection techniques of this research were interview with the pamong teacher, observation, and documentation such as photos and videos. The obtained data were then analyzed using quantitative and qualitative methods. Based on data analysis, there is the student participation improvement during learning processes for each indicator. Thus, the application of Teaching at the Right level approach proves capable of improving students’ participation during learning processes, particularly for Grade XII.10 at SMA 2 Makassar.